Aberrant movement‐related somatosensory cortical activity mediates the extent of the mobility impairments in persons with cerebral palsy. (6th July 2022) - Trevarrow, Michael P.; Taylor, Brittany K.; Reelfs, Anna M.; Wilson, Tony W.; Kurz, Max J.
Abstract : Abstract: There are numerous clinical reports showing that persons with cerebral palsy (CP) have proprioceptive, stereognosis, and tactile discrimination deficits. The current consensus is that these altered perceptions are attributable to aberrant somatosensory cortical activity. It has been inferred from these data that persons with CP do not adequately process ongoing sensory feedback during motor actions, which accentuates the extent of their mobility impairments. However, this hypothesis has yet to be directly tested. We used magnetoencephalographic brain imaging to address this knowledge gap by quantifying the somatosensory dynamics evoked by applying electrical stimulation to the tibial nerve in 22 persons with CP and 25 neurotypical controls at rest and during an ankle plantarflexion isometric force motor task. We also quantified the spatiotemporal gait biomechanics of participants outside the scanner. Consistent with the literature, our results confirmed that the strength of somatosensory cortical activity was weaker in the persons with CP compared to the neurotypical controls. Our results also showed that the strength of the somatosensory cortical responses were significantly weaker during the isometric ankle force task than at rest. Most importantly, our results showed that the strength of somatosensory cortical activity during the ankle plantarflexion force production task mediated the relationship between somatosensory cortical activity at rest and both walking velocity and step length. These results suggest that youth with CP have aberrant somatosensory cortical activity during isometric force generation, which ultimately contributes to the extent of mobility impairments seen in this patient population. Key points: Persons with cerebral palsy have reduced somatosensory cortical responses at rest and during movement. The somatosensory cortical responses during movement mediate the relationship between the somatosensory cortical responses at rest and mobility. Persons with cerebral palsy may have altered sensorimotor feedback that ultimately contributes to impaired mobility. Abstract : Abstract figure legend Magnetoencephalographic brain imaging was used to determine the effect of sensory feedback during movement on mobility in persons with cerebral palsy. Persons with cerebral palsy had reduced somatosensory cortical activity at rest and during movement compared with their neurotypical peers. Further, the somatosensory cortical activity during movement mediated the relationship between somatosensory cortical activity at rest and mobility. These results indicate that difficulties in sensorimotor integration may contribute to the mobility impairments seen in this patient population.